Safety and immunogenicity of adjuvanted recombinant subunit herpes zoster vaccine in lung transplant recipients. Issue 6 (6th March 2021) - Hirzel, Cedric; L'Huillier, Arnaud G.; Ferreira, Victor H.; Marinelli, Tina; Ku, Terrance; Ierullo, Matthew; Miao, Congrong; Schmid, D. Scott; Juvet, Stephen; Humar, Atul; Kumar, Deepali
Abstract : Lung transplant recipients are at high risk for herpes zoster and preventive measures are a significant unmet need. We investigated the safety and immunogenicity of two doses of a recombinant zoster vaccine (RZV) in lung transplant recipients (≥50 years). We enrolled 50 patients of which 49 received at least one vaccine dose. Anti‐glycoprotein E (gE) antibody levels (n = 43) increased significantly compared to baseline (median optical density [OD] 1.96; interquartile range [IQR]: 1.17–2.89) after the first (median OD 3.41, IQR 2.54–3.81, p < .0001) and second vaccine dose (median OD 3.63, IQR 3.39–3.86, p < .0001). gE‐specific polyfunctional CD4+ T cell frequencies (n = 38) also increased from baseline (median 85 per 10 6 CD4+ T cells; IQR: 46–180) to the first (median 128 per 10 6 CD4+ T cells; IQR: 82–353; p = .023) and after the second dose (median 361 per 10 6 CD4+ T cells; IQR: 146–848; p < .0001). Tenderness (83.0%; 95%CI: 69.2–92.4%) and redness (31.9%; 95%CI: 19.1–47.1%) at injection site were common. One rejection episode within 3 weeks of vaccination was observed. This is the first study demonstrating that RZV was safe and elicited significant humoral and cell‐mediated immunity in lung transplant recipients. RZV is a new option for the prevention of shingles in this population. Abstract : The inactivated shingles vaccine is safe and induces both antibody‐ and cell‐mediated responses in lung transplant recipients 50 years of age and older.